PENINGKATAN KINERJA PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA PERUSAHAAN FREIGHT FORWARDING DI JAWA TIMUR - , Eddy Santoso, Dr. Wakhid Slamet Ciptono, MBA, MPM. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The rapid development of businesses in services runs and related with the increasing levels of competition. The existence of the global financial crisis that occurred in some countries today, to some extent also affects the number of activities involving import export forwarder industry therein. Freight forwarding company is one of the companies that engaged in the service. Quality and service performance to be a determining factor to provide customer satisfaction that will ultimately make customers loyal to the company. Customer loyalty is a very important thing in an industry that both products and services. If customers are already loyal to a particular company then the customer will continue to use the products or services from these companies. Retain existing customers to remain loyal will certainly be important for industry players forwarder. The study was conducted with the aim to identify models of customer loyalty in the freight forwarding company in East Java, and also analyze the effect of service performance on customer loyalty that can be used as the basis for performance improvement. The research was conducted using path analysis method where the quality of service and service performance synergized with the factors that influence customer satisfaction and loyalty. These factors are perceived quality, perceived value, customer complaint, image, trust, and customer satisfaction. After testing with the SPSS 19, we got the result that there is a significant relationship between these constructs with loyalty. It can be concluded that turned out to customer loyalty in the freight forwarder company is influenced by the perceived value, perceived quality, customer satisfaction, trust, customer complaint and the image either directly or indirectly.